2013
DOI: 10.1371/journal.pone.0055608
|View full text |Cite
|
Sign up to set email alerts
|

Are NORs Always Located on Homeologous Chromosomes? A FISH Investigation with rDNA and Whole Chromosome Probes in Gymnotus Fishes (Gymnotiformes)

Abstract: Gymnotus (Gymnotiformes, Gymnotidae) is the most diverse known Neotropical electric knife fish genus. Cytogenetic studies in Gymnotus demonstrate a huge karyotypic diversity for this genus, with diploid numbers ranging from 34 to 54. The NOR are also variable in this genus, with both single and multiple NORs described. A common interpretation is that the single NOR pair is a primitive trait while multiple NORs are derivative. However this hypothesis has never been fully tested. In this report we checked if the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…3). Although a discussion of the ancestral condition of nucleolar organizer regions, with simple or multiple marking, has recently been proposed, 41 the great majority of species in which 18S rDNA was mapped, including the species in this study, present a terminal marking in the short arm of a subtelocentric/acrocentric pair, which suggests that they may be homologues.…”
Section: Discussionmentioning
confidence: 71%
“…3). Although a discussion of the ancestral condition of nucleolar organizer regions, with simple or multiple marking, has recently been proposed, 41 the great majority of species in which 18S rDNA was mapped, including the species in this study, present a terminal marking in the short arm of a subtelocentric/acrocentric pair, which suggests that they may be homologues.…”
Section: Discussionmentioning
confidence: 71%
“…The chromosome pairs GCA6 and 20 of GCA, 2n = 42 correspond to GCA11 and 20 in GCA, 2n = 40 and to GCP8 and 15. Milhomem et al [2013] demonstrated by 2-color FISH, using probes for 18S rDNA together with the WCP GCA20, that the association of rDNA and GCA20 is conserved and shared by all the studied species of Gymnotus of the G. carapo species group. G. jonasi , from the species group G. pantherinus or species group G1 [Lovejoy et al, 2010], has multiple NORs and does not share this association.…”
Section: Discussionmentioning
confidence: 88%
“…Among the Nannostomus species investigated here, chromosomal mapping revealed somewhat uniform patterns of distribution for both rDNA classes, with one to few sites of accumulation, as found in most fishes [93,94], as well as in some other lebiasinids [21,22] investigated to date. While some of these sites may appear to be orthologous among the species under study, the frequently high dynamics of these repetitive DNA classes do not allow us to make certain conclusions without additional data (for an exemplary study, see Milhomem et al [95]). Nonetheless, in addition to the fact that some rDNA sites were clearly involved in Robertsonian fusions (as mentioned above), it may be inferred that like some other related lebiasinids [19], Nannostomus species do not show a substantial level of intrachromosomal dynamics that could be detected by the markers selected by us.…”
Section: Discussionmentioning
confidence: 99%